Block-Parallel Chaotic Algorithms for Image Reconstruction - Gubareni, N.; Pleszczynski, M. (Электронное моделирование, 2009)
The paper is devoted to the elaboration and implementation of block-parallel asynchronous algorithms for computer tomography. The numerical reconstruction algorithms and numerical simulation results for a number of modeling objects and some particular systems of reconstruction are presented.